The Use of Imatinib Mesylate as a Lifesaving Treatment of Chronic Myeloid Leukemia Relapse after Bone Marrow Transplantation - Monika Conchon; Sabri S. Sanabani; Israel Bendit; Carla Luana Dinardo; Lucia Dias; Dalton de Alencar Fischer Chamone; Pedro Enrique Dorlhiac-Llacer; Frederico Luiz Dulley (Journal of Transplantation)
We describe the response of imatinib as lifesaving treatment of chronic myeloid leukemia (CML) relapse in seven patients who underwent allogeneic bone marrow transplantation (alloBMT) at our institution over a period of 4 years. Retrospective analysis of their medical records revealed that a mean age at transplant was 45.2 years. The median time to diagnosis was 7.4 years after transplant. At relapse, four, two, and one patients were classified as having hematologic, major molecular, and cytogenetic relapse, respectively. At imatinib initiation, five had CML in a chronic phase, while one patient was diagnosed as having accelerated phase and blast crisis. All these patients could be evaluated for the therapeutic efficacy. At a mean of follow-up of 1.9 years of therapy, all evaluable patients achieved major molecular response without compromising safety. Consistent with available data, our results indicate that imatinib is safe and effective treatment option for patients with relapse after BMT.